National Inspired or Locally Earned? The Locus of Local Political Support in a Multilevel Context - Steenvoorden, Eefje H.; van der Meer, Tom W. G. (Frontiers in Political Science, 2021)
Despite greater responsibility being passed to local and regional tiers of government in many European countries, we still have limited understanding about what shapes citizens' support for such tiers of government. On the one hand we expect citizens to evaluate local government on its own merits, depending on the performance of local units. Yet in the context of multi-layered governance, we argue that local political support is likely to be at least partly a derivative of attitudes to the national level. The Dutch Local Election Study 2016 offers us the possibility to test these expectations. We show that local political support is mainly (in the case of local democratic satisfaction) or substantially (in the case of local political trust) related to national political support. To the extent that local support is shaped by local evaluations, appraisals of output performance are more important than appraisals of input or throughput performance. There is some evidence that these relations are conditional. Political sophistication increases citizens' sensitivity to local performance. Yet, local embeddedness only modestly reduces citizens' reliance on national-level evaluations.